Cardiac Hydatidosis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Cardiac hydatid disease is rare, occurring in about 2 % of the patients, the disease usually involves the myocardium and is associated with a wide spectrum of presentations, hence the patients may be asymptomatic or may present with a serious condition like severe valvular dysfunction, congestive heart failure, pulmonary embolism or conductive disturbances. Full histories, a proper examination of the chest, ECG, CXR, Echocardiography, cardiac catheterization, CT scan of the chest and immunoblot tests are essential diagnostic tools. Fifteen patients diagnosed preoperatively as having cardiac hydatid cysts were involved in this retrospective study. There was neither sex predilection nor any age limit for the disease. Any part of the heart could be involved, but the Left ventricle was the commonest site. Many patients included in the study were associated with extracardiac involvement especially the liver. Removal of the cyst(s) surgically stays the treatment of choice.